Efectos de la contaminación del suelo por herbicidas en la productividad del arroz - Tenorio Gómez, Kleiner Marcelo (2020)
SUMMARY This document deals with what refers to soil contamination by herbicides does not cause effects on rice productivity. Rice cultivation is one of the main short-cycle products that are grown in our country, and that serve to meet the demand in food. From what was analyzed, it was determined that the impurities, present in several herbicides, also promote soil contamination, remaining for many years and causing the natural degradation of other pesticides, such as fungicides; the continuous entry of herbicides into the soil and plants, cause detrimental effects on soil microorganisms and their activity, which causes modification of the biological processes essential for the productivity of rice cultivation; the indiscriminate use of herbicides with high doses causes soil degradation; the herbicides Glyphosate and Atrazine, since the time of the Green Revolution, are considered to be the ones that cause the greatest damage in edaphoclimatic pollution; the persistence and dispersion of herbicides in the rice crop soil depends on the soil characteristics and climatic conditions; the agrochemicals used as Glyphosate Bispiribac, can considerably impact the organisms that are in charge of the decomposition of the soil and that serve to increase the productivity of the rice crop; the components that deteriorate the soil due to the use of herbicides are erosion by water and wind. These phenomena that cause in situ degradation of the soil, can be physical or chemical degradation processes and the effects of soil contamination by herbicides is the loss of biodiversity, which limits the phase of preparation of the land essential for agricultural development of rice cultivation.